Genetic markers of colour for determining the genetic structure of domestic cats (Felis catus) in rural areas of Lorica, Colombia - Causil Vargas, Luis Alfonso (2017)
The aim of this study was to analyse the genetic structure of domestic cats (Felis catus) in rural environments in Lorica, Colombia using morphological markers of colour. A phenotypic classification was made of 134 individuals distributed in three populations, attending to the presence or absence of the autosomal markers Non-agouti, Blotched tabby, Dilution, White spotting, Dominant white and the marker Orange linked to sex. The Blotched tabby marker was the most frequent and showed a possible natural selection, while Dominant white showed the lowest values. Populations showed absence of Hardy-Weinberg equilibrium. Moreover, an excess of homozygotes was evident, and differences between populations and scarce gene flow between populations was found. Polymorphism of genes that encode the colour of cats in rural habitats likely differ from domestic conditions in urban environment.